2008
DOI: 10.1088/0022-3727/42/2/025304
|View full text |Cite
|
Sign up to set email alerts
|

Structure–properties relationship in reactively sputtered Ag–Cu–O films

Abstract: Ag–Cu–O films were deposited on glass substrates by pulsed dc sputtering of a silver–copper target (Ag50Cu50) in reactive Ar–O2 mixtures. The film chemical composition was estimated by x-ray energy dispersive spectrometry and the structure was studied by x-ray diffraction (XRD). Optical properties (reflectance and transmittance) and room temperature electrical resistivity were evaluated using spectrophotometry and the four point probe method, respectively. Since silver atoms are less reactive versus oxygen tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For moderate to highly reactive chemical system, the reactive sputtering process comes with the abrupt decrease in the deposition rate when the sputter process turned in to so called reactive sputter mode [15]. Similar decrease in the deposition rate was also noticed in DC reactive sputtered Cu 2 O films deposited with copper target [16] and Ag-Cu-O films formed with Ag 50 Cu 50 target [10]. The chemical composition of the deposited films was determined by using energy dispersive X-ray analysis.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…For moderate to highly reactive chemical system, the reactive sputtering process comes with the abrupt decrease in the deposition rate when the sputter process turned in to so called reactive sputter mode [15]. Similar decrease in the deposition rate was also noticed in DC reactive sputtered Cu 2 O films deposited with copper target [16] and Ag-Cu-O films formed with Ag 50 Cu 50 target [10]. The chemical composition of the deposited films was determined by using energy dispersive X-ray analysis.…”
Section: Resultssupporting
confidence: 53%
“…Pititjean et al [9] reported on the influence of annealing temperature on the decomposition, and structural and properties relationship in reactively sputtered Ag 2 Cu 2 O 3 films formed with Ag 50 Cu 50 sputter target. Pititjean et al [10][11][12] studied the effect of oxygen flow rate on the structure and properties of pulsed DC sputtered Ag-Cu-O films deposited using Ag 60 Cu 40 target. The effect of deposition temperature on the structural and optical properties of RF magnetron sputtered Ag 70 Cu 30 target was systematically studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…For moderate to highly reactive chemical system, the reactive sputter process comes with the abrupt decrease in the films deposition rate when the process turned into the so-called reactive sputter mode [16]. Such a decrease in the deposition rate with the increase of oxygen partial pressure was also reported in the deposition of DC reactive magnetron sputtered silver oxide films [17] formed with silver target, cuprous oxide films [18] formed with copper target and Ag-Cu-O films with Ag 50 Cu 50 target [19]. Figure 2 shows the representative X-ray energy dispersive spectrum of the Ag-Cu-O film formed of oxygen partial pressure of 2 × 10 −2 Pa.…”
Section: Resultsmentioning
confidence: 73%
“…The interatomic distance (R) and its associated coordination number (N) for the Ag-Ag, Ag-O, and Au-Au pairs were set to 0.288 9 nm with the N value of 12 [29], 0.204 4 nm with the N value of 2 [30], and 0.288 4 nm with the N value of 12 [31], respectively. The many-body reduction factor S 0 2 was assumed to be equal for both the sample and the reference.…”
Section: Page 11 Of 39mentioning
confidence: 99%